PENGEMBANGAN VIDEO PEMBELAJARAN MENGGUNAKAN CANVA UNTUK MENINGKATKAN PEMAHAMAN MATERI CAHAYA DAN SIFATNYA KELAS V SD MUHAMMADIYAH AMBARBINANGUN - Danan Ikhwan Kurniansyah; Urip Muhayat Wiji Wahyudi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to develop a CANVA-based Learning Video on the topic of light and its properties, in order to improve the understanding of fifth-grade elementary school students. In addition, this study also aims to determine the level of feasibility, practicality, and effectiveness of Canva-based Learning Video media used in the learning process. This study is a development research using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) with a One-Group Pretest-Posttest Design. The limited test subjects consisted of 5 fifth-grade students of Muhammadiyah Ambarbinanguan Elementary School, while the broad test involved 24 students in the 2025/2026 academic year. Data collection techniques were carried out through interviews, questionnaires, and tests. Data analysis used a descriptive qualitative and quantitative approach with the help of SPSS 26, including validity tests, reliability tests, normality tests, and Paired Sample t-Tests. The results of this study indicate that CANVA-based learning videos received very positive responses from material experts, media experts, teachers, and students. The level of media feasibility is categorized as very feasible with a score of 84% from material experts and 90% from media experts. This media is also considered practical with a response of 83% from teachers and 74.25% from students. In addition, the Learning Video has proven effective in improving student understanding, as shown by the results of the Paired Sample t-Test with a significance value of 0.000 < 0.05, so there is a significant difference between the pretest and posttest scores.